2014
DOI: 10.1515/ijamh-2013-0337
|View full text |Cite
|
Sign up to set email alerts
|

Association of oral hygiene habits and food intake with the risk of dental caries among undergraduate university women in Saudi Arabia

Abstract: The results of this study are useful for public health intervention programs to combat dental caries in the Saudi community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Amin and Al‐Abad observed that maternal working conditions, large family size and poor oral hygiene practices were the chief predictors for dental caries among Saudi school‐going children. The frequent intake of milk, fruit and vegetables was found to protect against dental caries, whereas the consumption of chocolate and soft drinks for the same period was found to be a risk factor for dental caries among undergraduate university women from Saudi Arabia . Studies on diverse global populations have also linked multiple socio‐economic factors including male gender, education, income, dietary habits and medication, with the occurrence of dental caries .…”
Section: Discussionmentioning
confidence: 99%
“…Amin and Al‐Abad observed that maternal working conditions, large family size and poor oral hygiene practices were the chief predictors for dental caries among Saudi school‐going children. The frequent intake of milk, fruit and vegetables was found to protect against dental caries, whereas the consumption of chocolate and soft drinks for the same period was found to be a risk factor for dental caries among undergraduate university women from Saudi Arabia . Studies on diverse global populations have also linked multiple socio‐economic factors including male gender, education, income, dietary habits and medication, with the occurrence of dental caries .…”
Section: Discussionmentioning
confidence: 99%
“…This is due to their religion as many Jain individuals avoid brushing their teeth, especially during fasting. [9] It has been shown that toothbrushing frequency is associated with a higher risk of caries[10111213] and periodontal diseases. [14151617] However, frequencies of mechanical removal of plaque up to 24 h were reported to be enough to prevent an increase in the severity of gingival inflammation (in patients with no history of periodontitis).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that young females in Saudi Arabia are likely to neglect oral hygiene habits and follow poor dietary habits. [29] Economic rush has been considered an important factor in changing dietary and oral health habits of the Saudis. [30] However, one should be careful in interpreting the results of this study since Al Madinah is a cosmopolitan city and its residents come from almost all over the Muslim world.…”
Section: Discussionmentioning
confidence: 99%